A component of excitation-contraction coupling triggered in the absence of the T671-L690 and L720-Q765 regions of the II-III loop of the dihydropyridine receptor alpha(1s) pore subunit. - Ahern, C A (2001)
We conducted a deletion analysis of two regions identified in the II-III loop of alpha(1S), residues 671-690, which were shown to bind to ryanodine receptor type 1 (RyR1) and stimulate RyR1 channels in vitro, and residues 720-765 or the narrower 724-743 region, which confer excitation-contraction (EC) coupling function to chimeric dihydropyridine receptors (DHPRs). Deletion mutants were expressed in dysgenic alpha(1S)-null myotubes and analyzed by voltage-clamp and confocal fluo-4 fluorescence. Immunostaining of the mutant subunits using an N-terminus tag revealed abundant protein expression in all cases. Furthermore, the maximum recovered charge movement density was >80% of that recovered by full-length alpha(1S) in all cases. Delta671-690 had no effect on the magnitude of voltage-evoked Ca(2+) transients or the L-type Ca(2+) current density. In contrast, Delta720-765 or Delta724-743 abolished Ca(2+) transients entirely, and L-type Ca(2+) current was reduced or absent. Surprisingly, Ca(2+) transients and Ca(2+) currents of a moderate magnitude were recovered by the double deletion mutant Delta671-690/Delta720-765. A simple explanation for this result is that Delta720-765 induces a conformation change that disrupts EC coupling, and this conformational change is partially reverted by Delta671-690. To test for Ca(2+)-entry independent EC coupling, a pore mutation (E1014K) known to entirely abolish the inward Ca(2+) current was introduced. alpha(1S) Delta671-690/Delta720-765/E1014K expressed Ca(2+) transients with Boltzmann parameters identical to those of the Ca(2+)-conducting double deletion construct. The data strongly suggest that skeletal-type EC coupling is not uniquely controlled by alpha(1S) 720-765. Other regions of alpha(1S) or other DHPR subunits must therefore directly contribute to the activation of RyR1 during EC coupling.